Possession of Household Firearms and Firearm-Related Discussions with Clinicians Among Veterans Receiving VA Mental Health Care. (3rd February 2020) - Valenstein, Marcia; Walters, Heather; Pfeiffer, Paul Nelson; Ganoczy, Dara; Ilgen, Mark Andrew; Miller, Matthew Jason; Fiorillo, Matthew; Bossarte, Robert M.
Abstract : Objectives: To assess possession of household firearms among veterans receiving mental health care and the frequency of their discussions with clinicians about firearms. Methods: We surveyed random samples of veterans receiving mental health care in each of five purposively chosen, geographically diverse VA facilities; 677 (50% of recipients) responded. Results: 45.3% (95% CI 41.2, 49.3) of veteran respondents reported household firearms; 46.9% of those with suicidal thoughts and 55.6% with a suicide plan had household firearms. Only 27.5% of all veteran respondents and 44% of those with recent suicidal ideation and household firearms had had a firearm-related discussion with a clinician. Discussion: Many veterans receiving mental health care can readily access firearms, a highly lethal means for suicide. Increasing clinician-patient discussions and health system efforts to reduce firearm access might reduce suicide in this clinical population.